Listening to sea lions : currents of change from Galapagos to Patagonia - Meltzoff, Sarah K. (AltaMira Press, 2013)
From the Galapagos to the depths of Patagonia and up along the stark desert coast of Chile, Listening to Sea Lions' empathic ethnography carries the reader directly into the heart of the ocean world of Latino coastal people. Sea lions are the fellow denizens in nature who share the perpetual changes and are seen as metaphoric selves. Meltzoff uses storytelling rather than explicit theory to help explain local struggles and survival strategies wrought by extreme El Niño events and shifting political cli.